2x+3=x-t

Simple and best practice solution for 2x+3=x-t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3=x-t equation:


Simplifying
2x + 3 = x + -1t

Reorder the terms:
3 + 2x = x + -1t

Reorder the terms:
3 + 2x = -1t + x

Solving
3 + 2x = -1t + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3 + 2x + -1x = -1t + x + -1x

Combine like terms: 2x + -1x = 1x
3 + 1x = -1t + x + -1x

Combine like terms: x + -1x = 0
3 + 1x = -1t + 0
3 + 1x = -1t

Add '-3' to each side of the equation.
3 + -3 + 1x = -3 + -1t

Combine like terms: 3 + -3 = 0
0 + 1x = -3 + -1t
1x = -3 + -1t

Divide each side by '1'.
x = -3 + -1t

Simplifying
x = -3 + -1t

See similar equations:

| (-9)+85= | | 2x+3=6x-17 | | 2.3*7.6= | | 8(b+1)= | | f(x)=7x^2+42 | | 3-a=12 | | .05(-y+200)+.1y=14 | | (x+85)+(x+113)=180 | | 4(2x*-7)=8x-3 | | 9x^2+21xy-8y^2=0 | | H(x)=7x^4+3x^3-2x^2-x+1 | | 8(1+4x)=-40+8x | | y+14=4y+5 | | 6(8)=9(x-2) | | w+1-4w+8=21 | | 10=4x+2x+2 | | 12(6)+3= | | 0.7x+0.6y=43 | | 11(6)+9= | | 40-6x=3x-5 | | 1.4u-6.5=.5 | | 15+22t-5t^2=0 | | -4x-2y=26 | | (11x+9)=(12x+3) | | -10+6=-7x-9 | | 2x-5y=-280 | | 2r-(5-r)=13r+2r | | 12(x-6)=5(7) | | 0.8(x-6.1y-2)= | | 5(x+5)(x-5)= | | 12(-0.52)+3= | | y=6x^2+7x-20 |

Equations solver categories